Case report: Childhood epilepsy and borderline intellectual functioning hiding an AADC deficiency disorder associated with compound heterozygous DDC gene pathogenic variants - Cursio, Ida; Siliquini, Sabrina; Carducci, Claudia; Bisello, Giovanni; Mastrangelo, Mario; Leuzzi, Vincenzo; Bertoldi, Mariarita; Marini, Carla (Frontiers in Neurology, 2023)
Aromatic L-amino acid decarboxylase (AADC) deficiency is a rare autosomal recessive neurometabolic disorder leading to severe combined serotonin, dopamine, norepinephrine, and epinephrine deficiency. We report on a female patient with borderline functioning and sporadic clearcut focal to bilateral seizures from age 10 years. A neuropsychological assessment highlighted a mild impairment in executive functions, affecting attention span and visual-spatial abilities. Following the diagnosis of epilepsy with a presumed genetic aetiology, we applied a diagnostic approach inclusive of a Next Generation Sequencing (NGS) gene panel, which uncovered two variants in trans in the dopa decarboxylase (DDC) gene underlying an AADC deficiency. This compound heterozygous genotype was associated to a mild reduction of homovanillic acid, a low level of the norepinephrine catabolite, and a significant reduction of 5-hydroxyindoleacetic acid in cerebrospinal fluid.Remarkably, 3-O-methyldopa (3-OMD) and 5-hydroxytryptophan were instead increased. During the genetically guided reevaluation process, some mild signs of dysautonomic dysfunction (nasal congestion, abnormal sweating, hypotension and fainting, excessive sleepiness, small hands and feet and increased level of prolactin, tiredness and fatigue) more typical of AADC deficiency, were evaluated with a new insight.Of the two AADC variants, the R347Q has already been characterized as a loss-of-function with severe catalytic impairments, while the novel L391P variant has been predicted to have a less severe impact. Bioinformatic analyses suggest that the amino acid substitution may affect affinity for PLP coenzyme. Thus, the genotype corresponds to a phenotype with mild and late onset symptoms of which seizures were the clinical sign, leading to medical attention. This case report expands the spectrum of AADC deficiency phenotypes to encompass a less disabling clinical condition including borderline cognitive functioning, drug-responsive epilepsy, and mild autonomic dysfunction.